Abandonado no meio do deserto como um santo que Deus largou em plena penitência: das raízes do romantismo aos Lugares do Sagrado na obra de Caio Fernando Abreu - Dias, Cleberson (2022)
This thesis is divided into three movements. The first – the flesh – proposes to analyze, based on his biography, interviews, letters and chronicles, the spaces that “Holy” occupies in the life of Brazilian writer Caio Fernando Abreu. “Between acts”, the second movement – the spirit – deals with the author based on the assumptions of Romanticism: his work announces the primacy of emotion over reason, outlining a kind of literature that seeks the inside and the “meeting” with Nature. The third and last movement – the sacred – is rebuilt in the mirroring of the first and the second, verifying its implications in the narrative elements of two literary works: Triângulo das Águas and Onde andará Dulce Veiga? The hypotheses: the almost obsessive interest in the “Other Thing” results in a literature committed to elevating the spirit. Towards Infinity. The writer is a late twentieth-century romantic, who seeks God, and his poetry incorporates aspects of the new spiritual movements